Qualidade analítica EDXRF e WDXRF para materiais aluminossilicatados sob avaliação da preparação e menor quantidade da amostra - CASTANHO, Rebeca Soares (2019)
Systematic and optimized sample preparation methods guarantee the analytical quality of the measurements, as well as serve as a reference parameter for the instruments used. This case study aimed to establish the best preparation condition and the smallest amount of sample in pressed powder method for instrumental X-ray fluorescence spectrometry technique using reference aluminosilicate materials: two kaolins and one basalt. In order to do this, the aim was to define the best pressure during pressing, the best proportion of binder, to test liquid (oil) and solid (plastic film) release agents and to check the advantage of pressed powders under vacuum. The pressed powder method was also compared with the fused glass bead method, as well as the two following measurement equipments: Wavelength Dispersive X-Ray Fluorescence (WDXRF) and Energy Dispersive X-Ray Fluorescence (EDXRF). From the factorial experimental design 33x2 = 54 trials, only 22 kaolin pressed powder pellets were equated for analysis, with fairly accurate values for: SiO2, Al2O3, Fe2O3, Na2O e TiO2 as well as based on physical characteristics of the sample (firmness and thickness) the best condition were: 3g of sample, 30% of wax, 25 ton of pressure under vacuum to use oil as a release agent. These conditions were satisfactorily reproduced in triplicates for the kaolins and the basalt. The results revealed that the smallest amount that guarantees an analytical quality in this case study was 0.5 g. With respect to the comparison about the best sample preparation method, if fused glass bead or pressed powder, there were no significant differences in the results as well as there were no significant differences between the results obtained by EDXRF and WDXRF equipments. Thus, it can be concluded that the more economical analytical conditions such as sample in the form of pressed powder and benchtop spectrometer EDXRF can provide good quality semiquantitative chemical responses.